Effect of acclimation on performance and metabolism of female hockey players during intermittent running in the heat - Sunderland, C. (Loughborough University, 2001)
The impact of heat acclimation on performance of high intensity intermittent exercise, that is representative of team sports has not been extensively studied. The performance of skills during team sports is also important in the outcome of a match or competition. The research presented in this thesis was undertaken to investigate the impact of heat acclimation on female performance of high intensity intermittent running and field hockey skill. The first experimental study investigated the effect of the menstrual cycle and oral contraceptive use on performance of high intensity intermittent running in the heat. Seven normally menstruating women and eight oral contraceptive users participated in the study. Two trials were undertaken near the predicted mid-point of the follicular (FT) and luteal (LT) phases of the menstrual cycle and the equivalent days for the oral contraceptive users. There were no differences in distance run between menstrual cycle phases or between the normally menstruating and oral contraceptive groups (follicular vs luteal phase; 5869 ± 2896 vs 6238 ± 2648 m). Plasma glucose concentrations were higher in the follicular phase than the luteal, (main effect phase P<0.01), while serum growth hormone concentrations were lower (main effect phase P<0.05). These results demonstrate that for unacclimatised games players the performance of intermittent, high intensity shuttle running in the heat is unaffected by menstrual cycle phase nor oral contraceptive use.